Cenozoic basin evolution of the Central Patagonian Andes: Evidence from geochronology, stratigraphy, and geochemistry - Encinas, A. (2019)
The Central Patagonian Andes is a particular segment of the Andean Cordillera that has been subjected to the subduction of two spreading ridges during Eocene and Neogene times. In order to understand the Cenozoic geologic evolution of the Central Patagonian Andes, we carried out geochronologic (U-Pb and 40Ar/39Ar), provenance, stratigraphic, sedimentologic, and geochemical studies on the sedimentary and volcanic Cenozoic deposits that crop out in the Meseta Guadal and Chile Chico areas (∼47°S). Our data indicate the presence of a nearly complete Cenozoic record, which refutes previous interpretations of a hiatus during the middle Eocene–late Oligocene in the Central Patagonian Andes. Our study suggests that the fluvial strata of the Ligorio Márquez Formation and the flood basalts of the Basaltos Inferiores de la Meseta Chile Chico Formation were deposited in an extensional setting related to the subduction of the Aluk-Farallon spreading ridge during the late Paleocene–Eocene. Geochemical data on volcanic rocks interbedded with fluvial strata of the San José Formation suggest that this unit was deposited in an extensional setting during the middle Eocene to late Oligocene. Progressive crustal thinning allowed the transgression of marine waters of Atlantic origin and deposition of the upper Oligocene–lower Miocene Guadal Formation. The fluvial synorogenic strata of the Santa Cruz Formation were deposited as a consequence of an important phase of compressive deformation and Andean uplift during the early–middle Miocene. Finally, alkali flood basalts of the late middle to late Miocene Basaltos Superiores de la Meseta Chile Chico Formation were extruded in the area in response to the suduction of the Chile Ridge under an extensional regime. Our studies indicate that the tectonic evolution of the Central Patagonian Andes is similar to that of the North Patagonian Andes and appears to differ from that of the Southern Patagonian Andes, which is thought to have been the subject of continuous compressive deformation since the late Early Cretaceous.